PENYULUHAN SISTEM RUJUKAN PELAYANAN KESEHATAN - Devi Purnamasari; Agus Salim; Widya Azzari; Rizka Bagiana (Awal Bros Journal of Community Development, 2021)
Referral system for health services is the implementation of services health which regulates the delegation of duties and responsibilities of services health reciprocally both vertically and horizontally. Referral system mandatory for patients who are insurance participants health or social health insurance and health care providers. In this article, the author describes community service activities that have been carried out to increase public understanding of the health service referral system . Community service activities carried out in the area Kulim, Kulim District of using the method of lecture, discussion and question and answer. As for the results of this community activity, the community has been able to understand the referral system for health services. This activity can also Increase public awareness of the enthusiastic or health checks as well as the right to Increase public awareness of healthy living